The Effect Of Human Resource Development, Organizational Culture, And Total Participation On Asn Employee Performance In The Regional Financial And Asset Agency Of North Sumatera Province - Ria Suryani Saragih; Kholilul Kholik; Emi Wakhyuni (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aimed to analyze the effects of human resource development, organizational culture, and total participation on the performance of civil servant employees at the Regional Financial and Asset Agency of North Sumatra Province. This study used a quantitative approach with an associative method. The research population consisted of 95 civil servant employees, and the sample also included 95 respondents selected using a saturated sampling technique. Primary data were collected through the distribution of questionnaires, and the results were processed using SPSS software version 24. Data analysis was conducted using multiple linear regression to examine the relationships between the independent variables and the dependent variable. The results showed that human resource development, organizational culture, and total participation, both partially and simultaneously, had positive and significant effects on employee performance. Human resource development became the most dominant variable influencing employee performance, as it had the highest regression coefficient. The regression analysis produced the equation Y = 6.656 + 0.301X1 + 0.210X2 + 0.185X3 + e. The t-test results indicated that human resource development had a t-value of 3.771 with a significance value of 0.000. Organizational culture had a t-value of 2.695 with a significance value of 0.008, while total participation had a t-value of 2.941 with a significance value of 0.004. The F-test result showed an F-value of 102.138 with a significance value of 0.000. Hypotheses H1, H2, H3, and H4 were proven to be correct and acceptable, as the research findings were consistent with the proposed hypotheses. The coefficient of determination (adjusted R²) of 0.763 indicated that 76.3% of the variation in employee performance could be explained by the three independent variables, while the remaining variation was explained by other variables not included in this research model. In addition, the strength of the relationship between the independent variables and the dependent variable was categorized as very strong, with a correlation coefficient (R) value of 0.878.